Family futures : childhood and poverty in urban neighbourhoods - Power, Anne; Willmot, Helen; Davidson, Rosemary (Bristol ; Portland : Policy Press, 2011)
Based on a unique longitudinal study, this timely book examines the initiatives introduced to help families and the impacts on them, their future prospects and the implications for policy.
Family roles in community matters -- Schools in communities -- Young people, space, facilities and activities -- Preventive policing, community safety and community confidence -- Family health and neighbourhood conditions -- Families move into work : skills, training and tax credits -- Housing and regeneration -- How the areas are changing.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Poor families -- Longitudinal studies; Urban poor -- Longitudinal studies; Poor children -- Longitudinal studies; Poor families -- Services for -- Longitudinal studies; Urban poor -- Services for -- Longitudinal studies; Poor children -- Services for -- Longitudinal studies; Families -- Economic aspects -- Longitudinal studies